THE EFFECTS OF JOB SATISFACTION TO INTENTION TO LEAVE - Romadhoni, Yahya Tri; Noermijati, Noermijati; Moko, Wahdiyat; Nazzal, Ayman (Universitas Brawijaya, Indonesia, 2020)
This research aimed to test and analyze the effects of job satisfaction to intention to leave through the mediation of organizational commitment and moderation of alternative job opportunities. The researchers exerted a quantitative method in this research. The research data was collected through a questionnaire, while the data sampling was the technique of saturated sampling. The sample in this research was taken from all employees in PT. Supraharmonia Consultindo with a minimum of a work period of a year and a total of 106 respondents. The data analysis in this research was the method of Partial Least Square (PLS) and the 3.0 SmartPLS program. The result showed that job satisfaction did not affect significantly to the intention to leave. Meanwhile, the job satisfaction affected significantly to the organizational commitment and the organizational commitment affected significantly to the intention to leave. Moreover, the organizational commitment was able to mediate the effects of job satisfaction and intention to leave. Whilst, the alternative job opportunities did not moderate the effect of job satisfaction and intention to leave.Next research in diverse places can give complexity results and add new variables like job stress and leadership.